Portability of Supplementary Pension Rights in Europe: A Lowest Common Denominator Solution. (March 2015) - Guardiancich, Igor
Abstract : In its effort to guarantee the free movement of workers, the European Union devised an advanced system of coordination of social security rights. Since 1958, statutory pensions are being aggregated for workers moving across the Member States. However, until mid‐2014, the portability of supplementary pension rights was not assured, there by undermining the freedom to labor mobility. This impaired the efficient allocation of labor, prevented sound family planning, infringed the fundamental right to social protection and during the Great Recession, hindered the employability of workers across a slowly recovering Europe. After nine years of negotiations, the EU has finally passed a Portability Directive, which is, however, a watered down version of the 2005 original proposal. Given such state of affairs, this study has three aims. First, it explains why portability of supplementary pensions, as opposed to the coordination of statutory ones, has been neglected and contested for a long time. Second, it illustrates the shortcomings of a patchy coordination‐without‐portability regime. Third, it enumerates the characteristics of the Portability Directive passed by the European Parliament in April 2014, and the strategic steps undertaken to secure its final adoption.